Implantação de um serviço de farmacovigilância hospitalar e comparação dos algoritmos para análise de reação adversa a medicamento - Varallo, Fabiana Rossi [UNESP] (2014)
Spontaneous reports by health professionals generate signals in pharmacovigilance. However, the passive method has limitations and the most important of them are underreporting and poor quality of data, hindering the causality assessment of adverse drug events (ADE). Therefore, the present study aimed to validate an educational intervention (EI) in pharmacovigilance for hospital professionals, in order to analyze the impact on knowledge, skill and attitude of the staff and to compare the causality´s categories of adverse drug reactions (ADR) with different decision algorithms. Then, we performed a longitudinal not randomized study which was conducted in four phases. The first one corresponded to the validation of EI with undergraduate students of the Pharmacy course and post-graduation students of the Public Health of the School of Pharmaceutical Sciences- UNESP, in September and October/2011. We proposed a multifaceted EI which was developed in four meetings with one hour each one. The following activities were carried out: application of a questionnaire to assess the knowledge, skill and attitude before and after EI; lecture; practical class and education material distribution. Answers of questionnaire and minimum and desired criteria to fill the ADE form were analyzed and compared with definitions of World Health Organization and Pan American Health Organization, which were considered gold-standard answers. The second phase comprised the development of EI for professionals (medical staff, nursing and multidisciplinary team) of the Hospital Estadual Américo Brasiliense, among February and April/2012, as well as the follow up of the number of reports made during 12 months before and after EI. Third phase was the intensive monitoring of ADR by screening of medical records with nine of 24 trigger tools developed by the Institute for Healthcare Improvement, in order to calculate ADR underreporting rate. Fourth phase was the ADR causality ...